2010
DOI: 10.1007/s11899-009-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in Myelodysplastic Syndromes: An Erythropoiesis-Stimulating Agent or More?

Abstract: Anemia remains the most challenging clinical manifestation to treat in patients with lower-risk myelodysplastic syndromes (MDS). Erythropoiesis-stimulating agents are widely used to treat anemia in such patients, but less than one third respond to these agents, and the duration of response is often limited. Lenalidomide, a second-generation immunomodulatory drug (IMiD), is approved by the US Food and Drug Administration for treatment of transfusion-dependent anemia in lower-risk MDS patients with deletion 5q c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…As erythropoiesis improved in control mice, it is unclear if the improvement in Rps6 heterozygously-deleted mice is specific. The lack of understanding of the mode of action of lenalidomide in 5q-syndrome MDS, the suggestion that the erythroid response may be mediated in part by haploinsufficiency of two phosphatase genes located on 5q[23] independent of a ribosome biogenesis defect, and the drug’s clinical risk of causing neutropenia and thrombocytopenia underscore the importance of animal models for testing its therapeutic efficacy in DBA. Our studies establish Rps6 heterozygously-deleted mice as one available model.…”
Section: Resultsmentioning
confidence: 99%
“…As erythropoiesis improved in control mice, it is unclear if the improvement in Rps6 heterozygously-deleted mice is specific. The lack of understanding of the mode of action of lenalidomide in 5q-syndrome MDS, the suggestion that the erythroid response may be mediated in part by haploinsufficiency of two phosphatase genes located on 5q[23] independent of a ribosome biogenesis defect, and the drug’s clinical risk of causing neutropenia and thrombocytopenia underscore the importance of animal models for testing its therapeutic efficacy in DBA. Our studies establish Rps6 heterozygously-deleted mice as one available model.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these results suggest that active therapy may help to lower supportive care requirements, and may also help to reduce disease-specific resource utilization by lowering the risk of MDS-related adverse clinical events. Interestingly, recent data suggest that active therapy, and not supportive care [14,15], may in fact alter the natural history of these bone marrow failure malignancies [8,16,17]. It appears that both transfusion needs and active therapy may contribute to the utilization of disease-specific medical resources by this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…96 In patients with del(5q) MDS, lenalidomide suppresses abnormal clonal expansion by inhibiting M-phase inducer phosphatase 3 and protein phosphatase 2A, resulting in lenalidomide-specific apoptosis. 97,98 Lenalidomide regulates other critical pathways, including regulators of the cytoskeleton and tumoursuppressor genes, encoded for within the del(5q) region, which may account for some of its direct antitumour and immunomodulatory properties. 97,98 A randomized phase III study of lenalidomide versus placebo in red blood cell transfusion-dependent patients with low-risk or intermediate-risk MDS and del(5q) showed that more patients in the lenalidomide groups achieved transfusion independence (primary end point) compared with placebo (56.1% and 42.6%; P <0.001), while also attaining high cytogenetic response rates of 50.0% (lenalidomide 10 mg) versus 25.0% (lenalidomide 5 mg; P = 0.066).…”
Section: Del(5q) Myelodysplastic Syndromementioning
confidence: 99%